Cyber Crime According to the ITE Law - Ismail Koto (International Journal Reglement & Society (IJRS), 2021)
The development of this information technology in turn changes the social order and behavior. In fact, it does not only end there, but also changes the reality of the economy, culture, politics and law. Therefore, behind the positive benefits, internet technology also has a small negative impact. One of them is used as a means of committing crimes, hereinafter known as internet crime or cybercrime. The procedure used to collect data in this study is in the form of documentation, namely the guidelines used in the form of notes or quotes, searching legal literature, books and others related to the identification of problems in this study offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. In relation to the regulation of criminal penalties for cybercrime in Indonesia, until now the majority of cybercrime acts in Indonesia have not been regulated in clear legal norms in the legislation, therefore in adjudicating cybercrime the provisions of the Criminal Code and provisions in laws outside the Criminal Code are applied. Provisions in the Criminal Code that can be used to prosecute cybercrimes by means of extensive interpretation are provisions concerning the crime of counterfeiting (as regulated in Articles 263 to 276), the crime of theft (as regulated in Articles 362 to 367), criminal acts of fraud ( how it is regulated in Articles 378 to 395), and criminal acts of destruction of goods (as regulated in Articles 407 to 412). Law Number 11 of 2008 concerning Information and Electronic Transactions (IET). The rules of criminal acts committed in it are proven to threaten internet users. Since the enactment of Law no. 11 of 2008 concerning Information and Electronic Transactions on April 21, 2008, has caused many victims. Based on the monitoring that has been carried out by the alliance, there are at least four people who are called the police and become suspects because they are suspected of committing criminal acts stipulated in the ITE Law.